Integritas Pendidikan Karakter Dalam Pembelajaran IPS - Anisa Fitriani Mutmainah; Apip Rudianto; Suhara, Djenal; Martini, Susi (MURABBI, 2022)
Character education is needed to form attitude, personality and morals of a nation. In its application character education can be applied through the learning process one of which is in learning social science. The study aims to determine the role of social science in the formation of learners character and to know the application or implementation of character education in social science. This research method uses literature, literature research methods though various agreed procedures. The results of this study are educators or teachers and schools play an important role in shaping the character of students through schools rules, activities that are followed and learning process. Character education is applied to students through social science tailored to the material and conditions of students. Learning methods and teacher understanding of the material also affect the development of character education. In learning social science also has the same goal as character education which is to create good citizens and have moral values.